Complex functional surface design for additive manufacturing - Morris, S.J.; Dudman, J.P.R.; Körner, L.; Melo, P.; Newton, L.H.; Clare, Adam T. (2016)
This paper presents a new methodology for the creation of advanced surfaces which can be produced by Additive Manufacturing (AM) methods. Since there is no cost for enhanced complexity, AM allows for new capabilities in surface design. Micro-scale surface features with varying size, shape and pitch can be manufactured by Two-Photon Polymerisation (2PP). Computer-Aided Design (CAD) tools allowing for this variation to be incorporated into the surface design are only just emerging. With the presented methodology, surfaces are created from a single feature design. Variation is applied to the surface features through algorithmic design tools, allowing for arrays of hundreds of unique features can be created by non-CAD experts. The translation of these algorithmic expressions from CAD to a physical surface is investigated. Using the proposed methodology, 2PP is used to create quasi stochastic surfaces for the purpose of enhancing the biointegration of medical implants against current state-of-the-art.